Effects of active referral combined with a small financial incentive on smoking cessation: study protocol for a cluster randomised controlled trial - Weng, Xue (BMJ Open, 2020)
INTRODUCTION: Evidence-based smoking cessation treatments are effective but underutilised, accentuating the need for novel approaches to increase use. This trial investigates the effects of active referral combined with a financial incentive to use smoking cessation services on smoking abstinence among community smokers. METHODS AND ANALYSIS: This ongoing study is a two-arm, assessor-blinded, pragmatic, cluster randomised controlled trial with follow‐ups at 1, 2, 3 and 6 months after randomisation. We aim to enrol 1134 daily smokers from 70 community sites (clusters) in Hong Kong. All participants receive Ask, Warn, Advise, Refer, Do-it-again (AWARD) guided advice and a self-help booklet at baseline. Additionally, participants in the intervention group receive an offer of referral to smoking cessation services at baseline and a small financial incentive (HK$300≈US$38) contingent on using any of such services within 3 months. The primary outcomes are bioverified abstinence (exhaled carbon monoxide <4 ppm and salivary cotinine <10 ng/mL) at 3 and 6 months. Secondary outcomes include self-reported 7-day point prevalence of abstinence, smoking reduction rate, quit attempts and the use of smoking cessation services at 3 and 6 months. Intention-to-treat approach and regression models will be used in primary analyses. ETHICS AND DISSEMINATION: This protocol has been approved by the Institutional Review Board of the University of Hong Kong/Hospital Authority Hong Kong West Cluster (IRB reference number: UW 18-318). The results of this trial will be submitted for publication in peer-reviewed journals, and the key findings will be presented at national and international conferences. TRIAL REGISTRATION NUMBER: ClinicalTrials.gov Registry NCT03565796.